Micro electronic systems via multifunctional additive manufacturing. Issue 4 (14th May 2018) - Li, Ji; Wasley, Thomas; Ta, Duong; Shephard, John; Stringer, Jonathan; Smith, Patrick J.; Esenturk, Emre; Connaughton, Colm; Harris, Russell; Kay, Robert
Abstract : Purpose: This paper aims to demonstrate the improved functionality of additive manufacturing technology provided by combining multiple processes for the fabrication of packaged electronics. Design/methodology/approach: This research is focused on the improvement in resolution of conductor deposition methods through experimentation with build parameters. Material dispensing with two different low temperature curing isotropic conductive adhesive materials was characterised for their application in printing each of three different conductor designs, traces, z -axis connections and fine pitch flip chip interconnects. Once optimised, demonstrator size can be minimised within the limitations of the chosen processes and materials. Findings: The proposed method of printing z -axis through layer connections was successful with pillars 2 mm in height and 550 µm in width produced. Dispensing characterisation also resulted in tracks 134 µm in width and 38 µm in height allowing surface mount assembly of 0603 components and thin-shrink small outline packaged integrated circuits. Small 149-µm flip chip interconnects deposited at a 457-µm pitch have also been used for packaging silicon bare die. Originality/value: This paper presents an improved multifunctional additive manufacturing method to produce fully packaged multilayer electronic systems. It discusses the development of new 3D printed, through layer z -axis connections and the use of a single electrically conductive adhesive material to produce all conductors. This facilitates the surface mount assembly of components directly onto these conductors before stereolithography is used to fully package multiple layers of circuitry in a photopolymer.